Diagnostic tests for the detection of human papillomavirus-associated cervical lesions - Reuschenbach, Miriam; Knebel Doeberitz, Magnus von (Current pharmaceutical design, 2013)
Current diagnostic approaches for primary cervical cancer screening, work-up of equivocal or positive screening results or follow- - up after treatment of precancerous lesions primarily rely on the morphologic interpretation of squamous epithelial cells (Pap cytology), - in some setting accompanied by the detection of human papillomavirus DNA and have largely contributed to remarkable reduction - of disease incidence in countries with implemented screening programs. However, these approaches are limited by a poor sensitivity and - reproducibility of Pap cytology and low specificity for high grade cervical intraepithelial neoplasia of HPV DNA detection assays. Early - detection might be improved by complementing or even replacing these tests by markers which are more directly related to molecular - events triggering HPV-induced carcinogenesis and thereby might deliver more accurate diagnostic performance. The delineation of molecular - changes which occur during different stages of HPV infections and the identification of changes which induce neoplastic alterations - allow for the detection of markers that specifically highlight the transforming stage of the infection where viral oncogenes are overexpressed - and therefore allow for a more specific diagnosis of lesions that require treatment. The evaluation of such markers in clinical - studies revealed that some indeed show an improved diagnostic performance compared to Pap cytology or HPV DNA tests only.